God Save Texas: A Journey into the Soul of the Lone Star State - Lawrence Wright (Vintage; Reprint edition, 2019)
God Save Texas is a journey through the most controversial state in America. It is a red state, but the cities are blue and among the most diverse in the nation. Oil is still king, but Texas now leads California in technology exports. Low taxes and minimal regulation have produced extraordinary growth, but also striking income disparities. Texas looks a lot like the America that Donald Trump wants to create.